Prevalence of multidrug resistant bacteria in causing community acquired urinary tract infection among the patients attending outpatient department of Seti Zonal Hospital, Dhangadi, Nepal - Awasthi, Tek Raj; Pant, Narayan Dutt; Dahal, Puspa Raj (Nepal Journal of Biotechnology, 2015)
Involvement of multidrug resistant bacteria in causing community acquired infection is very serious public health issue. The main objective of our study was to determine the prevalence of multidrug resistant bacteria in causing community acquired urinary tract infection. In this study we cultured the 384 mid stream urine samples collected aseptically from the patients attending outpatient department of Seti zonal hospital and having no past history of hospitalization. The organisms isolated were identified by using conventional biochemical tests and antimicrobial susceptibility testing was performed by Kirby Bauer disc diffusion technique. Out of total 384 samples 98 (25.52%) samples showed significant bacterial growth. The most prevalent bacterium isolated was Escherichia coli. 42.86% of the bacteria isolated were found to be multidrug resistant (MDR). The involvement of such large numbers of multidrug resistant bacteria in causing community acquired urinary tract infection is very serious issue and cannot be neglected. And some abrupt initiatives should be taken by the responsible authorities to improve or at least avoid the further worsening of the situation. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 55-59